2020
DOI: 10.1186/s12893-020-00856-y
|View full text |Cite
|
Sign up to set email alerts
|

Five gene signatures were identified in the prediction of overall survival in resectable pancreatic cancer

Abstract: Background Although genes have been previously detected in pancreatic cancer (PC), aberrant genes that play roles in resectable pancreatic cancer should be further assessed. Methods Messenger RNA samples and clinicopathological data corrected with PC were downloaded from The Cancer Genome Atlas (TCGA). Resectable PC patients were randomly divided into a primary set and a validation set. Univariable Cox regression analysis, lasso-pena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
(63 reference statements)
1
8
0
Order By: Relevance
“…Wu et al [ 28 ] coincided with the present results as they found the AADAC gene to be one of five survival-related genes significantly upregulated and significantly correlated with overall survival (OS) in resectable pancreatic cancer (PC) by using the TCGA database followed by multivariant analysis. They explained their results as the protein coded by AADAC protein is extensively implicated in the hydrolysis of various drugs [ 9 ], whose function may be related to chemotherapy resistance in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 86%
“…Wu et al [ 28 ] coincided with the present results as they found the AADAC gene to be one of five survival-related genes significantly upregulated and significantly correlated with overall survival (OS) in resectable pancreatic cancer (PC) by using the TCGA database followed by multivariant analysis. They explained their results as the protein coded by AADAC protein is extensively implicated in the hydrolysis of various drugs [ 9 ], whose function may be related to chemotherapy resistance in pancreatic cancer.…”
Section: Discussionsupporting
confidence: 86%
“…ADRA2A is thought to be involved in the progression of multiple cancer and can inhibit the activation of PI3K/Akt/mTOR pathway [23]. AADAC is a kind of serine hydrolase widely involved in the hydrolysis of drugs and associated with poor prognosis in stomach adenocarcinoma [24,25]. More future studies are needed to gain more insights into these genes.…”
Section: Discussionmentioning
confidence: 99%
“…ROC curves of 1, 3, and 5 years were plotted with the survivalROC R package. Then, we conducted the performance comparison of the signature in our study (referred to as TP53Sig) with eight recently published signatures: 6-mRNA signature from Hou’s study (referred to as HouSig) [ 18 ], 4-mRNA signature from Meng’s study (referred to as MengSig) [ 19 ], 8-mRNA signature from Meng’s study (referred to as MengSig) [ 20 ], 5-mRNA signature from Wu’s study (referred to as WuSig) [ 21 ], 7-mRNA signature from Wu’s study (referred to as WuSig) [ 22 ], 10-mRNA signature from Yue’s study (referred to as YueSig) [ 23 ], 2-mRNA signature from Zhou’s study (referred to as ZhouSig) [ 24 ] and 6-LncRNA signature from Deng’s study (referred to as DengSig) [ 25 ]. ROC curves of 3 years were plotted and AUC values were calculated using the survivalROC R package.…”
Section: Methodsmentioning
confidence: 99%